Perbandingan Pendapatan Usahatani Jagung Berdasarkan Etnis Petani Di Desa Sidodadi Kecamatan Sangkub Kabupaten Bolaang Mongondow Utara - Kapantow, Firka Kesya; Katiandagho, Theodora Maulina; Rori, Yolanda Pinky Ivanna (Sam Ratulangi University, 2024)
This study aims to identify the comparison of corn farming income based on the ethnicity of farmers in Sidodadi Village, Sangkub Subdistrict, North Bolaang Mongondow Regency. The data collection method used in this research is primary data obtained through direct interviews to respondents and secondary data obtained from relevant government agencies in the research location. Sampling sampling used is Simple Random Sampling (Simple random sample) the sample is taken randomly. which will be sampled as many as 15 samples consisting of 5 Javanese Ethnic, 5 Minahasa Ethnic, and 5 Gorotalo Ethnic. The results of this study indicate that the highest total income of each ethnicity is Javanese Ethnicity with a total income of IDR 4,420,714 and the lowest total income is Gorontalo Ethnicity with a total income of IDR 1,635,625.